2017
DOI: 10.1007/s00367-017-0492-8
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic stability evaluation and seismic triggering scenarios of submerged slopes in Lake Zurich (Switzerland)

Abstract: If you would like to know when your article has been published online, take advantage of our free alert service. For registration and further information, go to: .Due to the electronic nature of the procedure, the manuscript and the original figures will only be returned to you on special request. When you return your corrections, please inform us, if you would like to have these documents returned. Dear AuthorHere are the proofs of your article.• You can submit your corrections online, via e-mail or by fax.• … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 46 publications
(29 reference statements)
2
57
0
Order By: Relevance
“…The relief and structure of the tip slope is varied and mainly related to the development of surface mass movements (Rucińska 2015; Rudowski et al 2016) commonly reported in the areas of the continental slope (inter alia Hampton et al 1996;McAdoo et al 2000;Canals et al 2004;Baeten et al 2013), underwater slopes of volcanic, tectonic and glacial lakes (inter alia Gardner et al 2000;Strupler et al 2017), and of large river deltas (inter alia Prior & Suhayda 1979;Nemec 1990;Biscara et al 2012). The inventory and nature of these forms is very similar, although of course the scale as well as the structure of the slope is different.…”
Section: Discussionmentioning
confidence: 99%
“…The relief and structure of the tip slope is varied and mainly related to the development of surface mass movements (Rucińska 2015; Rudowski et al 2016) commonly reported in the areas of the continental slope (inter alia Hampton et al 1996;McAdoo et al 2000;Canals et al 2004;Baeten et al 2013), underwater slopes of volcanic, tectonic and glacial lakes (inter alia Gardner et al 2000;Strupler et al 2017), and of large river deltas (inter alia Prior & Suhayda 1979;Nemec 1990;Biscara et al 2012). The inventory and nature of these forms is very similar, although of course the scale as well as the structure of the slope is different.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in acoustic character and breaks in the continuity of seismic reflections provide valuable information on defining limits of intact stratigraphy, zones of removed sediment and disruption of transported sediment (e.g. Alves & Cartwright 2009;Alves et al 2014;Strupler et al 2017). While this enables better demarcation of evacuation and depositional zones, any measurement of length that is based solely on coarsely-spaced 2D seismic data (or 2D outcrops for that matter) will be an 'apparent' measurement, and is thus likely to be an underestimate.…”
Section: Differentiating Evacuation From Depositional Zonesmentioning
confidence: 99%
“…5. Example of frontally-confined landslides in Lake Zurich (modified from Strupler et al 2017). Volumes based on thickness measurements from multibeam data are a factor of 3 less than those calculated from seismic data.…”
Section: Challenges In Calculating Landslide Volumesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving to inland waters, the risk of tsunami from lacustrine landslides is sometimes noted, yet remains poorly researched in the literature. Some exceptions include recent assessments for European lakes (Strasser et al 2011;Hilbe & Anselmetti 2015;Strupler et al 2017;Strupler et al 2018). Perhaps this is due to subaqueous geohazard organizations and their research ships having a stronger focus on marine environments and developments.…”
Section: Assessments Of Subaqueous Mass Movements In Lakes Fjords Anmentioning
confidence: 99%